Imaging of the medial rectus muscle predicts the development of optic neuropathy in thyroid eye disease - Marcel Berger; Juliane Matlach; Susanne Pitz; Manfred Berres; Franz Axmacher; George J. Kahaly; Marc A. Brockmann; Matthias Müller-Eschner (Scientific Reports, 2022)
Abstract Goal of the study was to evaluate bony orbit remodeling and extraocular muscle (EOM) volume in thyroid eye disease (TED) and their role as predicting factors for development of dysthyroid optic neuropathy (DON). Orbital computed tomography of 92 patients with TED with (76 orbits) or without DON (98 orbits) were retrospectively evaluated. Orbits (n = 40) of subjects without TED served as controls. Measurements of the bony orbit as well as EOM volume were incorporated into a generalized linear mixed model to predict DON. The angle of the medial orbital wall was significantly smaller (p < 0.001) in patients with TED (− 2.3 ± 3.6°) compared to patients with TED + DON (1.0 ± 4.1°). Both groups differed significantly from controls (− 4.2 ± 2.7°). Bowing of the medial orbital wall correlated positively with muscle volume (r = 0.564; p < 0.001). Total EOM volume was significantly larger in TED + DON (7.6 ± 2.5cm3) compared to TED only (5.6 ± 3.0cm3; p < 0.001) or controls (2.6 ± 0.5cm3). Multivariate analysis revealed the medial rectus muscle volume (TED: 1.06 ± 0.48cm3 vs. TED + DON: 2.16 ± 0.84cm3) as the strongest predictor, achieving a specifity of 86.7% and a sensitivity of 73.7% in diagnosing DON in univariate analysis. Though characterized by a wide range of variability, increased medial rectus muscle volume is the strongest predictor for DON in our patient cohort with TED when analyzing a single muscle.